Evaluation of the new defined EFAS score (European foot and ankle society score) in relation to already established functional scores (FFI, MOXFQ) after cartilage reconstructive therapy (AMIC®) for osteochondral lesion of the talus. Issue 7 (October 2022) - Gottschalk, Oliver; Kerschl, Florian W.; Mazet, Judith; Suero, Eduardo; Hörterer, Hubert; Altenberger, Sebastian; Böcker, Wolfgang; Walther, Markus
Highlights: The European Foot and Ankle Society score correlates significantly with previously established functional scores. The EFAS seems to be a patient friendly questionnaire due to a smaller number of items compared to other PROMs. The autologous matrix-induced chondrogenesis (AMIC®) has shown good results in many short and long-term studies. Abstract: Background: In 2011, the European Foot and Ankle Society developed a Score (EFAS Score) to generate a standardized questionnaire for several European languages. The aim of this study is to analyse how the newly defined score correlates with already established function scores. Methods: This study is a monocentric prospective study. The questionnaires were completed at least 12 months postoperatively at the same time point. All patients had undergone surgery with the Autologous Matrix-Induced Chondrogenesis® procedure for osteochondral lesions of the talus. Results: A total of 69 patients (33 women, 36 men) participated in the study. The EFAS Score correlates very strongly with the Manchester–Oxford Foot Questionnaire (MOXFQ) and strongly with the Foot Function Index (FFI). Conclusion: This study shows that the EFAS Score correlates significantly with the FFI and the MOXFQ. The EFAS seems to be a more patient-friendly alternative due to fewer questions and response choices.